ACCLIMATIZATION OF LEARNING METHODS AND MEDIA IN STUDY GROUPS - Asyrofi, Mohammad Fathan; Amar, Saiful; Maslakha, Hidayatul; Istiqomah, Dwi Nur (Proceeding of International Conference of Islamic Education, 2024)
In the era of technological development and globalization, it is hoped that educators will be able to apply appropriate learning methods. Students will feel bored quickly if the learning methods applied are not appropriate. This research is a qualitative type of research using the literature study method. This research uses sources from various literature in the form of books, journals and other sources relevant to the topic raised. The results of this research are that educators or teachers must create creative learning methods to support the achievement of educational goals in Indonesia. This is necessary to attract students' interest in learning and eliminate boredom in learning. Among the learning methods that can be applied by educators include demonstrations, lectures, sociodrama, discussions, games, drills, field trips and group work. Then, during the learning process, media is needed as a means to apply learning methods. Among the media that can be used can be human-based, print-based, audio-visual and computer-based.